2019
DOI: 10.1111/cico.12394
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Race and Place in Economic Transactions: Findings from an Online Field Experiment

Abstract: Scholarship on discrimination consistently shows that non‐Whites are at a disadvantage in obtaining goods and services relative to Whites. To a lesser extent, recent work has asked whether or not place of residence may also affect individuals’ chances in economic markets. In this study, we use a field experiment in an online market for second‐hand goods to examine transactional opportunities for White, Black, Asian, and Latino residents of both advantaged and disadvantaged neighborhoods. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…At least one recent study has confirmed that neighborhood stigma exists independent of racial stigma (Besbris, Faber, & Sharkey, 2019). Indeed, this is the case for the "trailer trash" stigma discussed in this article which is primarily aimed at whites.…”
Section: Housing Stigma Neighborhood Stigma and Belongingsupporting
confidence: 62%
“…At least one recent study has confirmed that neighborhood stigma exists independent of racial stigma (Besbris, Faber, & Sharkey, 2019). Indeed, this is the case for the "trailer trash" stigma discussed in this article which is primarily aimed at whites.…”
Section: Housing Stigma Neighborhood Stigma and Belongingsupporting
confidence: 62%
“…Discriminatory policies fed racist ideas about black places (Hirsch 1983; Kendi 2016; Lipsitz 1998; Taylor 2019). Collective ideas about places—for example, negative stigma of poor communities of color (Besbris et al 2015; Besbris, Faber, and Sharkey 2019; Jones and Jackson 2012)—can carry consequences for residential choices.…”
Section: Introductionmentioning
confidence: 99%
“…U.S. metropolitan areas are defined by ethnoracial and socioeconomic segregation within and between neighborhoods (Krysan & Crowder, 2017;Massey & Denton, 1993;Quillian & Legrange, 2016;Reardon & Bischoff, 2011). As a result, neighborhoods with higher shares of poor and non-White households tend to be deprived of economic and institutional resources (Quillian, 2012;Sampson, 2012;Small & McDermott, 2006;Wilson, 1987) and their residents face various forms of exploitation, discrimination, and disadvantage (Besbris et al, 2015;Besbris et al, 2019;Desmond & Wilmers, 2019;Faber, 2019b;Quillian, 2014;Sharkey, 2013;Sharkey & Faber, 2014). Before, during, and after the Great Recession, more segregated neighborhoods experienced more subprime lending, more foreclosures, and an increase in the establishment of fringe financial institutions (Faber, 2018a(Faber, , 2018bWyly et al, 2009).…”
Section: External Shocks To the Housing Marketmentioning
confidence: 99%